1999
DOI: 10.1002/(sici)1097-461x(1999)74:3<315::aid-qua4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on the possible reaction pathway for the deacylation of the AChE-catalyzed reaction

Abstract: Acetylcholinesterase AChE -catalyzed hydrolysis of the Ž . neurotransmitter, acetylcholine ACh , occurs via an acylation and deacylation process. The deacylation process was studied theoretically by the semiempirical quantum chemical method AM1 using the model molecules. To investigate the micro features of the deacylation process, two types of possible reaction mechanisms, the stepwise mechanism and the cooperative mechanism, were proposed and studied. All optimized structures of the model molecules for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Extensive experimental and computational studies have been reported on the reaction mechanism for AChE-catalyzed hydrolysis of ACh. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Most of the computational studies of the reaction coordinate have focused on the initial step of the acylation, 27 because this reaction step is the rate-determining step of the chemical process. The computational studies demonstrate how the protein environment can stabilize the transition state structure and, therefore, lower the energy barrier for this key reaction step of AChE-catalyzed hydrolysis of ACh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive experimental and computational studies have been reported on the reaction mechanism for AChE-catalyzed hydrolysis of ACh. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Most of the computational studies of the reaction coordinate have focused on the initial step of the acylation, 27 because this reaction step is the rate-determining step of the chemical process. The computational studies demonstrate how the protein environment can stabilize the transition state structure and, therefore, lower the energy barrier for this key reaction step of AChE-catalyzed hydrolysis of ACh.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial for rational design of high-activity BChE mutants against cocaine to know the detailed reaction mechanism concerning how cocaine is hydrolyzed by human BChE and to understand the mechanistic difference between BChE-catalyzed hydrolysis of cocaine and AChE-catalyzed hydrolysis of ACh. Extensive experimental and computational studies have been reported on the reaction mechanism for AChE-catalyzed hydrolysis of ACh. Most of the computational studies of the reaction coordinate have focused on the initial step of the acylation, because this reaction step is the rate-determining step of the chemical process. The computational studies demonstrate how the protein environment can stabilize the transition state structure and, therefore, lower the energy barrier for this key reaction step of AChE-catalyzed hydrolysis of ACh.…”
Section: Introductionmentioning
confidence: 99%
“…The results we have obtained help answer mechanistic questions posited by studies of other serine hydrolases; particularly the mechanism of proton transfer via His237, hydrogen bonding and charge stabilization in the oxyanion hole, and hydrogen bonding between His237 and Asp206 19,27 . Prior theoretical studies have found that the tetrahedral configuration in the acylation and deacylation reactions can correspond to TS or metastable intermediates, leading to either one or more dominant energetic barriers per reaction step [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] . We observe a single TS for each reaction step, coinciding with the tetrahedral configuration, which further supports that both the acylation and deacylation steps proceed in a concerted fashion in the PETase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…They also estimated the enzymatic catalytic effect with the semimicroscopic version of the Protein Dipoles Langevin Dipoles method . Wang et al studied both the acylation and the deacylation reactions with the semiempirical quantum chemical calculation method AM1. , Malany et al modeled theoretical free energies of a spherical ligand in the AChE active site with CHARMM22 to obtain electrostatic effects on catalysis and inhibition . Vagedes et al used the EVB method to probe the deacylation reaction .…”
Section: Carboxylic Ester Bond Hydrolysismentioning
confidence: 99%